Risks of Risk Communication: A Discursive Model for Crisis and Emergence Communication - Gallardo-Pauls, Beatriz (Círculo de Lingüística Aplicada a la Comunicación, 2021)
With the frame of reference of communicative experience imposed by the COVID-19, the article addresses the specificities of risk and crisis communication, with special attention to so called «crisis and emergence risk communication» (CERC). Likewise, the most developed theoretical models in this field, based on psychological and communication bases, are also reviewed from a discursive point of view. From this state of art, a specifically linguistic / discursive model of risk communication is proposed, capable of being considered as a defined area of ​​applied pragmatics. Such a model is deployed on two levels: the one that takes into account the discursive strategies in charge of textual framing (lexicon, syntax, illocutivity, informativeness and dialogism), and the one that defines the enunciative position from which the message is constructed (transparency, planning, disposition to audiences). The categories and functions of the two levels are presented through concrete examples referring to the management of the SARS-CoV-2 pandemic, the orderly review of which makes it possible to identify in each case some errors and unfortunate options that constitute true «risks of risk communication».